2014
DOI: 10.1073/pnas.1308963111
|View full text |Cite|
|
Sign up to set email alerts
|

Combined TRPC3 and TRPC6 blockade by selective small-molecule or genetic deletion inhibits pathological cardiac hypertrophy

Abstract: Significance Cardiac hypertrophy and dysfunction in response to sustained hormonal and mechanical stress are sentinel features of most forms of heart disease. Activation of non–voltage-gated transient receptor potential canonical channels TRPC3 and TRPC6 may contribute to this pathophysiology and provide a therapeutic target. Effects from combined selective inhibition have not been tested previously. Here we report the capability of highly selective TRPC3/6 inhibitors to block pathological hypertroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
163
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(168 citation statements)
references
References 37 publications
(51 reference statements)
2
163
1
Order By: Relevance
“…Pyr3 was also found to suppress DOX-induced ROS production by destabilizing Nox2 protein through disrupting the TRPC3-Nox2 complex formation in NRCMs ( Figure 5). As Pyr3 reportedly inhibits several other channels, such as CRAC channels and TREK and TASK2 potassium channels (24,38), it cannot be simply assumed that the effects of Pyr3 are mediated by disrupting the TRPC3-Nox2 interaction. However, our results clearly show that pharmacological effects by Pyr3 are quite similar to those by knockdown or genetic deletion of TRPC3 in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyr3 was also found to suppress DOX-induced ROS production by destabilizing Nox2 protein through disrupting the TRPC3-Nox2 complex formation in NRCMs ( Figure 5). As Pyr3 reportedly inhibits several other channels, such as CRAC channels and TREK and TASK2 potassium channels (24,38), it cannot be simply assumed that the effects of Pyr3 are mediated by disrupting the TRPC3-Nox2 interaction. However, our results clearly show that pharmacological effects by Pyr3 are quite similar to those by knockdown or genetic deletion of TRPC3 in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, two TRP canonical (TRPC) subfamily members, TRPC3 and TRPC6, reportedly participate in the development of pathological hypertrophy caused by neurohumoral factors (22,23) and mechanical stress (24)(25)(26). Our recent studies using TRPC-KO mice revealed that TRPC3, but not TRPC6, functions as a positive regulator of ROS, leading to induction of mechanical stress-induced maladaptive fibrosis (15,20,27).…”
Section: Introductionmentioning
confidence: 99%
“…Quantification of myocyte cross-sectional area, when performed in hematoxylin and eosin-stained sections, was performed with ImageJ. For wheat germ agglutinin (WGA) staining, slides were deparaffinized, rehydrated, and subjected to citrate-based heat-mediated antigen retrieval as previously described in (55). Sodium borohydride solution (1 mg/ml in PBS) was used for quenching.…”
Section: Mice Fbn1mentioning
confidence: 99%
“…Moreover, Pyr3 treatment also suppressed oxidative stress and cardiac fi brosis in mouse hearts with dilated cardiomyopathy, and mechanical stretch-induced production of ROS in rat cardiomyocytes. Two recently identifi ed selective TRPC3/6 inhibitors, GSK2332255B and GSK2833503A (IC 50 , 3-21 nM against TRPC3 and TRPC6), also inhibited ET-1-induced hypertrophic responses in adult cardiac myocytes [ 151 ]. These fi ndings strongly suggest that TRPC3 and TRPC6 are emerging as critical targets in the development of drugs relevant to therapies for pathological cardiac remodeling and chronic heart failure.…”
Section: Suppression Of Pathological Cardiac Hypertrophy By Trpc3/6 Imentioning
confidence: 92%
“…In contrast, pressure overloadinduced cardiac hypertrophy is suppressed by double deletions of TRPC3/6 genes in C57BL6/J background mice, although single deletion of TRPC3 and TRPC6 genes never suppresses cardiac hypertrophy [ 151 ]. As TRPC3 and TRPC6 form heteromultimer channels and regulate agonist-and mechanical stretch-induced hypertrophic growth of rat neonatal cardiomyocytes [ 35 ] and mice lacking TRPC6 were reported to have mRNA upregulation for TRPC3 [ 152 ], TRPC3 and TRPC6 proteins may compensatively work with each other.…”
Section: Role Of Trpc Channels In Pathological Cardiac Remodelingmentioning
confidence: 99%